A lithium-rich positive electrode material, a preparation method and application thereof

CN123017918APending Publication Date: 2026-10-30NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611099478.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-23
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

这种方案虽能提升材料的电子传输能力,但并未从根本上解决碳酸锂分解能垒高、分解不完全的核心问题,其补锂效率与容量仍无法满足应用要求;同时,高能球磨工艺存在能耗高、设备投入大、颗粒粒径与性能调控精度差、产品批次稳定性低等缺陷,难以适配规模化量产需求

Benefits of technology

(1)本发明提供了aLi2CO3·bLixMyOz·cMx1Oy1三相复合的富锂正极材料,Li2CO3与LixMyOz、Mx1Oy1形成紧密异质结界面,有效降低材料的本征电阻率,依托LixMyOz、Mx1Oy1的电化学介导催化作用,能够介导Li2CO3材料在较低电压下分解释放锂离子和电子,这种独特的“介导”机制成功突破了纯Li2CO3需要高电压自分解的限制,使其电化学分解平台电压降至≤4.6V,高度适配常规锂电工作窗口,实现Li2CO3在常规锂离子电池电压窗口内高效分解释锂。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123017918A_ABST
    Figure CN123017918A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of batteries, and relates to a lithium-rich positive electrode material and a preparation method and application thereof. x M y O z ·cM x1 O y1 , wherein M is selected from one or more of Zr, Mn, Cr, Ni, Ti, Co, Ru, Sn, Mo, Fe, Ge, Te, V, Cu, Zn and Al; a, b and c are molar fractions, a+b+c=1, a>=0.5, b>0 and c>0; x, y, z, x1 and y1 are positive integers satisfying the electrical neutrality of the compound, and the values thereof are determined by the specific M element and the valence state thereof. The lithium-rich positive electrode material has a low decomposition voltage and a high decomposition efficiency, and when used as a positive electrode active material of a battery, has excellent initial charge specific capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of battery technology and relates to a lithium-rich cathode material, its preparation method and application. Background Technology

[0002] Lithium-ion batteries, with their advantages of high energy density, long cycle life, low self-discharge, and no memory effect, have become the core power source for electric vehicles, portable electronic devices, and large-scale energy storage systems. During the first charge and discharge cycle of a lithium-ion battery, graphite, silicon-based, and other negative electrode materials undergo an irreversible solid-phase interface film formation reaction. This irreversibly consumes the active lithium ions extracted from the positive electrode, directly leading to a decrease in the battery's initial coulombic efficiency and irreversible capacity loss, severely limiting further improvements in battery energy density and cycle life. Introducing lithium-replenishing positive electrode active materials into the positive electrode, which release additional active lithium ions through decomposition during the first charge to compensate for the irreversible lithium loss from the negative electrode, is currently a hot topic in research and industrialization.

[0003] Currently, the main active materials used for lithium supplementation cathodes are iron-based lithium-rich oxide materials with the chemical formula Li5FeO4. For example, Chinese patent CN119911973A discloses Li5FeO4 and its application as a lithium supplementation additive. Although Li5FeO4 has a high theoretical lithium supplementation capacity, it is extremely sensitive to air. When exposed to air, it easily reacts with water vapor and carbon dioxide, losing its activity. Therefore, its storage, transportation, and application processes have extremely stringent requirements, limiting its application.

[0004] Lithium carbonate-based cathode lithium replenishment materials exhibit excellent chemical stability in air and low raw material costs, making them highly promising materials for industrialization. However, their practical applications are limited by their decomposition potential, which is typically above 4.7 V, exceeding the operating voltage window of conventional lithium batteries (generally around 4.3 V). Furthermore, their poor intrinsic conductivity and high energy barrier to electrochemical decomposition make it difficult to exhibit electrochemical activity. To improve the conductivity defects of lithium carbonate, existing technologies propose high-energy ball milling composites of lithium carbonate and conductive carbon materials to prepare lithium carbonate / carbon composites. For example, Chinese patent CN118522973A discloses a lithium carbonate / carbon composite material that improves conductivity by mixing lithium carbonate with conductive carbon black and ball milling it. While this approach can improve the electron transport capability of materials, it does not fundamentally solve the core problems of high energy barrier and incomplete decomposition of lithium carbonate. Its lithium replenishment efficiency and capacity still cannot meet application requirements. At the same time, the high-energy ball milling process has defects such as high energy consumption, large equipment investment, poor particle size and performance control precision, and low batch stability of products, making it difficult to adapt to the needs of large-scale mass production.

[0005] In summary, existing positive electrode active materials for lithium replenishment generally suffer from defects such as poor air stability, poor compatibility with existing production processes, mismatch between decomposition voltage and conventional lithium battery operating window, low decomposition efficiency, and incomplete decomposition. The industry urgently needs a new type of lithium-rich positive electrode material that combines excellent air stability, fast decomposition efficiency, low decomposition voltage, and simple preparation. Summary of the Invention

[0006] In view of the problems existing in the prior art, the purpose of this invention is to provide a lithium-rich cathode material, its preparation method and application.

[0007] The present invention employs the following technical solutions to achieve its objective: A lithium-rich cathode material includes an electrochemically active material comprising lithium carbonate, lithium metal oxide, and a metal oxide; the lithium metal oxide has the chemical formula Li. x M y O z The chemical formula of the metal oxide is M x1 O y1 The electrochemically active material is composed of the empirical formula aLi₂CO₃·bLi x M y O z ·cM x1 O y1 The expression indicates that M is selected from one or more of Zr, Mn, Cr, Ni, Ti, Co, Ru, Sn, Mo, Fe, Ge, Te, V, Cu, Zn, and Al; a, b, and c are mole fractions, a+b+c=1, a≥0.5, b>0, and c>0; x, y, z, x1, and y1 are positive integers that satisfy the electrical neutrality of the compound, and their values ​​are determined by the specific M element and its valence state.

[0008] Li2CO3 and Li x M y O z M x1 O y1 A tight heterojunction interface is formed between them: firstly, it reduces the intrinsic resistivity of the material; secondly, during charging, Li... x M y O z M x1 O y1 As an electrochemically active component, it can mediate the decomposition of Li2CO3 materials at relatively low voltages, releasing lithium ions and electrons. This "mediating" mechanism overcomes the limitation that pure Li2CO3 requires high voltage for self-decomposition.

[0009] Preferably, M x1 O y1 Li is obtained by heating and decomposing the carbonate of M in an oxygen-containing atmosphere.x M y O z By M x1 O y1 It is obtained by heating Li2CO3 in an oxygen-containing atmosphere. The oxygen-containing atmosphere can be an oxygen atmosphere or an air atmosphere.

[0010] In the lithium-rich cathode material, Li₂CO₃ is the main component, with a content ≥ 0.5%, to ensure high capacity. Preferably, a = 0.5~0.9, 0 < b ≤ 0.4, and 0 < c ≤ 0.4. As examples, a can be any one of 0.5, 0.55, 0.6, 0.65, 0.7, 0.8, 0.85, or 0.9, or a range between any two values; more preferably, 0.6 ≤ a ≤ 0.9. As examples, b can be any one of 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, or 0.4, or a range between any two values; more preferably, 0.05 ≤ b ≤ 0.3. As an example, c can be any one of 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4 or a range between any two values, with a further preferred value of 0.05≤c≤0.2.

[0011] Preferably, M is selected from one or more of Zr, Mn, Ni, Ti, Co, and Mo. When M is Ni, the composition of the electrochemically active material is represented by the empirical formula aLi₂CO₃·bLiNiO₂·cNiO; when M is Co, the composition of the electrochemically active material is represented by the empirical formula aLi₂CO₃·bLiCoO₂·cCo₃O₄; when M is Mn, the composition of the electrochemically active material is represented by the empirical formula aLi₂CO₃·bLi₂MnO₃·cMnO₂; when M is Zr, the composition of the electrochemically active material is represented by the empirical formula aLi₂CO₃·bLi₂ZrO₃·cZrO₂; when M is Mo, the composition of the electrochemically active material is represented by the empirical formula aLi₂CO₃·bLi₂MoO₃·cMoO₂; and when M is Ti, the composition of the electrochemically active material is represented by the empirical formula aLi₂CO₃·bLi₂TiO₃·cTiO₂.

[0012] Preferably, the electrochemically active material is prepared by chemical precipitation, wherein the median particle size is 500 nm to 5 μm.

[0013] Preferably, the electrochemical decomposition voltage of the lithium-rich cathode material is ≤4.6V. It can be selected as 3.5~4.55V.

[0014] Preferably, when the lithium-rich cathode material is used as a positive electrode active material in a battery and is first charged within a 2.5V to 4.5V window, its charge specific capacity is ≥ 400 mAh / g.

[0015] The second aspect of this invention provides a method for preparing the above-mentioned lithium-rich cathode material, comprising the following steps: A water-soluble M salt and a water-soluble lithium salt are mixed and dissolved in water to form a mixture. A carbonic acid source is then added, and the mixture is reacted to obtain a slurry containing M carbonate and Li2CO3. The slurry is dried to obtain a powder. The powder is then sintered in air or an oxygen atmosphere to obtain the electrochemically active material.

[0016] This invention employs a chemical precipitation method to prepare nano-sized lithium-rich cathode materials. During the preparation process, all elements are atomically homogeneously mixed, resulting in a uniform distribution of elements in the final product and effectively avoiding performance defects caused by elemental segregation. Simultaneously, the resulting product has a small median particle size, significantly increasing the reaction interface and shortening the Li⁺ electron transport path, thereby improving the material's lithium replenishment efficiency and catalytic activity. Furthermore, this preparation method is simple to operate, requires minimal investment in production hardware, eliminates the need for complex equipment, and is easily scalable for mass production, reducing industrial production costs.

[0017] Preferably, the water-soluble M salt is one or more of the acetate and oxalate of M.

[0018] Preferably, the water-soluble lithium salt is one or more of lithium acetate, lithium oxalate, and lithium hydroxide.

[0019] Preferably, the molar ratio of water-soluble M salt to water-soluble lithium salt is 1:4 to 100. The lithium source should be dominant to ensure high capacity of the material.

[0020] Preferably, the concentration of water-soluble lithium salt in the mixture is 0.1~2 g / mL. The concentration of the prepared solution should not be too high, as this is detrimental to the refinement and uniformity of the material.

[0021] The carbonate source is used to react with water-soluble M salt and water-soluble lithium salt to generate the corresponding M carbonate and Li2CO3. Preferably, the carbonate source is one or both of ammonium carbonate and ammonium bicarbonate.

[0022] The molar amount of carbonate source added is 1.05 to 2.5 times the theoretical amount of carbonate required for complete precipitation of lithium ions and metal M ions to form the corresponding carbonate. A slight excess of carbonate source is necessary to ensure complete precipitation of Li and M.

[0023] Preferably, the reaction is carried out at 5~50°C, more preferably at room temperature; the reaction is carried out with stirring at 100~1000 rpm for 10~200 min.

[0024] The drying process includes oven drying, spray drying, vacuum drying, etc. Spray drying is preferred as it can further refine the particles and improve their electrochemical performance.

[0025] Preferably, the sintering temperature is 200~800℃; the heating rate is 2~8℃ / min; the sintering atmosphere is air or oxygen, more preferably an oxygen atmosphere, to efficiently remove impurity elements; and the sintering time is 1~10h. The specific range of sintering temperature and sintering time depends on the selected M element. By controlling the sintering temperature and sintering time, Li2CO3 and Li can be obtained. x M y O z M x1 O y1 Three-phase composite materials.

[0026] The third aspect of the present invention provides the application of the above-mentioned lithium-rich cathode material, which can be used alone as the positive active material of the positive electrode sheet of a lithium-ion battery, or added to the positive electrode sheet as a lithium replenishing material to compensate for the irreversible lithium loss during the first charge and discharge of the battery.

[0027] A fourth aspect of the present invention provides a positive electrode sheet, comprising a positive current collector and a positive electrode layer disposed on at least one side surface of the positive current collector, wherein the positive electrode layer comprises the lithium-rich positive electrode material, a binder, and a conductive agent; Alternatively, the positive electrode sheet includes a positive current collector and a positive electrode film disposed on at least one side surface of the positive current collector. The positive electrode film includes a positive active material, a binder, a conductive agent, and a lithium supplementation additive, wherein the lithium supplementation additive is the lithium-rich positive electrode material. Alternatively, the positive electrode sheet may include a positive current collector, a positive active layer, and a lithium-rich positive electrode material layer disposed on the positive active layer. The positive active layer may include a positive active material, a binder, and a conductive agent. The lithium-rich positive electrode material layer may be composed of the lithium-rich positive electrode material.

[0028] Preferably, the positive electrode active material is one or more selected from lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium nickel cobalt manganese oxide ternary materials, and lithium-rich manganese-based materials. The binder is one or more selected from polyvinylidene fluoride, sodium carboxymethyl cellulose, and styrene-butadiene rubber. The conductive agent is one or more selected from conductive carbon black, carbon nanotubes, and graphene.

[0029] Preferably, in the positive electrode layer, the mass ratio of the lithium-rich positive electrode material, binder, and conductive agent is 80~96:1~10:1~10. In the positive electrode film or positive electrode active layer, the mass ratio of the positive electrode active material, binder, and conductive agent is 80~96:1~10:1~10.

[0030] Preferably, in the positive electrode film, the lithium-rich positive electrode material accounts for 0.5 to 10 wt% of the total mass of the positive electrode film. More preferably, it accounts for 1 to 5 wt%.

[0031] Preferably, the lithium-rich cathode material layer accounts for 0.5 to 10 wt% of the total mass of the cathode active layer. More preferably, it accounts for 1 to 5 wt%.

[0032] The positive electrode sheet satisfies the following characteristics: After assembling the positive electrode into a battery and performing the first charge-discharge cycle, the Li₂CO₃ in the lithium-rich positive electrode material completely decomposes, and the residual Li₂CO₃... x M y O z M x1 O y1 A porous conductive framework is formed and embedded in the positive electrode layer or positive electrode film.

[0033] A fifth aspect of the present invention provides a secondary battery comprising the above-described positive electrode, negative electrode, separator, and electrolyte.

[0034] Compared with the prior art, the present invention has the following beneficial effects: (1) This invention provides aLi2CO3·bLi x M y O z ·cM x1 O y1 Three-phase composite lithium-rich cathode material, Li2CO3 and Li x M y O z M x1 O y1 The formation of a tight heterojunction interface effectively reduces the intrinsic resistivity of the material, relying on Li x M y O z M x1 O y1 The electrochemically mediated catalysis can mediate the decomposition and release of lithium ions and electrons from Li2CO3 materials at lower voltages. This unique "mediation" mechanism successfully overcomes the limitation that pure Li2CO3 requires high voltage for self-decomposition, reducing its electrochemical decomposition platform voltage to ≤4.6V. This is highly compatible with the operating window of conventional lithium batteries, enabling Li2CO3 to efficiently decompose and release lithium within the voltage window of conventional lithium-ion batteries.

[0035] (2) The present invention uses chemical precipitation to prepare the lithium-rich cathode material. During the preparation process, atomic-level uniform mixing of each element is achieved, which effectively avoids the performance defects caused by element segregation. At the same time, the median particle size of the obtained product is low, which significantly increases the reactive interface of the material, greatly shortens the transport path of lithium ions and electrons, and thus effectively increases the reactive sites, improving the decomposition rate and decomposition completeness of the material.

[0036] (3) The lithium-rich cathode material of this invention uses Li2CO3 as the core component, exhibiting excellent chemical stability in air and electrolyte environments, thus solving the defects of traditional iron-based lithium-rich supplementary materials that are prone to moisture absorption and deactivation. This material can be used alone as a cathode active material or as a supplementary lithium additive in combination applications. The initial charge specific capacity is as high as 400 mAh / g or more, demonstrating extremely high lithium supplementation efficiency. Furthermore, when used as a cathode active material or supplementary lithium additive in lithium-ion batteries and subjected to the first charge and discharge cycle, the Li2CO3 in the material can be completely decomposed, while the residual Li x M y O z M x1 O y1 It can form a porous conductive framework in situ, improve the microscopic conductive structure of the positive electrode, and enhance the overall structural stability of the battery. Attached Figure Description

[0037] Figure 1 The XRD pattern of the product of Example 1; Figure 2 The XRD pattern of the product of Comparative Example 1; Figure 3 The image shows the XRD pattern of the product of Comparative Example 2.

[0038] Figure 4 This is a particle size distribution of the product from Example 1. Detailed Implementation

[0039] In the description of this invention, unless otherwise stated, the numerical range "a~b" represents a shortened representation of any combination of real numbers between a and b, and includes both a and b. "Multiple" includes two or more types, and can be two, three, four, five, or more.

[0040] The technical solution of the present invention will be further described and illustrated below with reference to specific embodiments and accompanying drawings. It should be understood that the specific embodiments described herein are only for the purpose of helping to understand the present invention and are not intended to limit the specific scope of the present invention. Furthermore, the accompanying drawings used herein are merely for better illustrating the content disclosed in the present invention and do not limit the scope of protection. Unless otherwise specified, the raw materials used in the embodiments of the present invention are all commonly used in the art, and the methods used in the embodiments are all conventional methods in the art.

[0041] The room temperature in this article is 20~22℃.

[0042] Example 1 (1) Weigh 0.07 mol lithium acetate and 0.01 mol nickel acetate in a molar ratio of Li:Ni=7:1, dissolve them in 40 mL of deionized water, add 0.1 mol ammonium carbonate, and stir continuously at 400 rpm for 1 h at room temperature to allow them to react and produce lithium carbonate and nickel carbonate.

[0043] (2) The slurry is spray-dried to obtain powder.

[0044] (3) The powder was heat-treated at 600℃ for 2 hours in O2 atmosphere (heating rate was 5℃ / min). After cooling, it was ground to obtain Li2CO3·LiNiO2·NiO composite material (the molar fraction of each component was approximately 0.75Li2CO3·0.15LiNiO2·0.1NiO).

[0045] The particle size range of the prepared Li₂CO₃·LiNiO₂·NiO composite material is as follows: Figure 4 As shown, the surface area is 2~3 μm. The specific surface area of ​​the prepared Li₂CO₃·LiNiO₂·NiO composite material is 2.7 m². 2 / g.

[0046] Figure 1 The XRD pattern of the product in Example 1 shows that the product is a three-phase composite of Li2CO3, LiNiO2, and NiO.

[0047] Example 2 (1) Weigh 0.05 mol lithium acetate and 0.01 mol cobalt acetate in a molar ratio of Li:Co=5:1, dissolve them in 35 mL of deionized water, add 0.08 mol ammonium bicarbonate, and stir continuously at 500 rpm for 1.5 h at room temperature to allow the two to react and generate lithium carbonate and cobalt carbonate.

[0048] (2) The slurry is spray-dried to obtain powder.

[0049] (3) The powder was heat-treated at 400℃ for 2 hours in an O2 atmosphere (heating rate of 4℃ / min). After cooling, it was ground to obtain Li2CO3·LiCoO2·Co3O4 composite material (the molar fraction of each component is approximately 0.65Li2CO3·0.25LiCoO2·0.1Co3O4).

[0050] The particle size range of the prepared Li2CO3·LiCoO2·Co3O4 composite material is 2~3μm.

[0051] The specific surface area of ​​the prepared Li₂CO₃·LiCoO₂·Co₃O₄ composite material is 2.8 m². 2 / g.

[0052] Example 3 (1) Weigh 0.09 mol lithium acetate and 0.01 mol manganese acetate in a molar ratio of Li:Mn=9:1, dissolve them in 50 mL of deionized water, add 0.12 mol ammonium carbonate, and stir continuously at 300 rpm for 0.5 h at room temperature to allow them to react and produce lithium carbonate and manganese carbonate.

[0053] (2) The slurry is spray-dried to obtain powder.

[0054] (3) The powder was heat-treated at 600℃ for 3 hours in O2 atmosphere (heating rate was 6℃ / min). After cooling, it was ground to obtain Li2CO3·Li2MnO3·MnO2 composite material (the molar fraction of each component was approximately 0.7Li2CO3·0.2Li2MnO3·0.1MnO2).

[0055] The particle size range of the prepared Li2CO3·Li2MnO3·MnO2 composite material is 2~3μm.

[0056] The specific surface area of ​​the prepared Li₂CO₃·Li₂MnO₃·MnO₂ composite material is 3.2 m². 2 / g.

[0057] Example 4 The difference between Example 4 and Example 1 is that step (3) of Example 4 is carried out in an air atmosphere, while the rest is the same as in Example 1.

[0058] Comparative Example 1 Steps (1) and (2) of Comparative Example 1 are the same as those of Example 1. Step (3) is: heat-treat the powder at 700°C for 2 hours in an O2 atmosphere (heating rate is 5°C / min), and after cooling, grind to obtain Li2CO3·LiNiO2 composite material (the molar fraction of each component is approximately 0.75Li2CO3·0.25LiNiO2).

[0059] Figure 2 The XRD pattern of the product in Comparative Example 1 shows that the product is a two-phase composite of Li2CO3 and LiNiO2.

[0060] Comparative Example 2 Steps (1) and (2) of Comparative Example 2 are the same as those of Example 1. Step (3) is: the powder is heat-treated at 400°C for 2 hours in an O2 atmosphere (heating rate is 5°C / min). After cooling, it is ground to obtain Li2CO3·NiO composite material (the molar fraction of each component is approximately 0.77Li2CO3·0.23NiO).

[0061] Figure 3 The XRD pattern of the product in Comparative Example 2 shows that the product is a two-phase complex of Li2CO3 and NiO.

[0062] Comparative Example 3 Steps (1) and (2) of Comparative Example 3 are the same as those of Example 2. Step (3) is: heat-treat the powder at 600°C for 2 hours in an O2 atmosphere (heating rate is 4°C / min), and after cooling, grind to obtain Li2CO3·LiCoO2 composite material (the molar fraction of each component is approximately 0.65Li2CO3·0.35LiCoO2).

[0063] Comparative Example 4 Steps (1) and (2) of Comparative Example 4 are the same as those of Example 2. Step (3) is: the powder is heat-treated at 200°C for 2 hours in an O2 atmosphere (heating rate is 4°C / min). After cooling, it is ground to obtain Li2CO3·Co3O4 composite material (the molar fraction of each component is approximately 0.85Li2CO3·0.15Co3O4).

[0064] Comparative Example 5 Steps (1) and (2) of Comparative Example 5 are the same as those of Example 3. Step (3) is: heat-treat the powder at 800°C for 3 hours in an O2 atmosphere (heating rate is 6°C / min), and after cooling, grind to obtain Li2CO3·Li2MnO3 composite material (the molar fraction of each component is approximately 0.78Li2CO3·0.22Li2MnO3).

[0065] Comparative Example 6 Steps (1) and (2) of Comparative Example 6 are the same as those of Example 3. Step (3) is: heat-treat the powder at 300°C for 3 hours in an O2 atmosphere (heating rate is 6°C / min), and after cooling, grind to obtain Li2CO3·MnO2 composite material (the molar fraction of each component is approximately 0.85Li2CO3·0.15MnO2).

[0066] Comparative Example 7 (1) Weigh 0.05 mol of lithium acetate and dissolve it in 35 mL of deionized water. Add 0.08 mol of ammonium carbonate and stir continuously at 400 rpm for 1 h at room temperature to produce lithium carbonate.

[0067] (2) The slurry is spray-dried to obtain powder.

[0068] (3) The powder was heat-treated at 600℃ for 2 hours in an O2 atmosphere (heating rate of 5℃ / min), and after cooling, it was ground to obtain Li2CO3 material.

[0069] Electrochemical performance testing: The composite materials prepared in the examples and comparative examples were mixed with conductive carbon black and PVDF at a mass ratio of 80:10:10, respectively. A uniform slurry was prepared using NMP as a solvent and coated onto the surface of aluminum foil to prepare a positive electrode. The active material loading of the electrode was approximately 2 mg / cm³. 2 CR2032 coin cells were assembled using lithium metal sheets as the counter electrode, with 1 mol / L LiPF6 electrolyte and a 1:1:1 volume ratio mixture of EC, EMC, and DMC as the electrolyte solvent. Constant current charge-discharge tests were conducted at a rate of 0.05C within a voltage range of 2.5–4.6 V to determine the initial charge specific capacity of the material. The results are shown in Table 1.

[0070] Table 1 Electrochemical performance of the examples and comparative examples

[0071] As shown in Table 1, the electrochemical performance of the Li₂CO₃·LiNiO₂·NiO composite material is superior to that of Li₂CO₃·LiNiO₂ and Li₂CO₃·NiO; the electrochemical performance of the Li₂CO₃·LiCoO₂·Co₃O₄ composite material is superior to that of Li₂CO₃·LiCoO₂ and Li₂CO₃·Co₃O₄; and the electrochemical performance of the Li₂CO₃·Li₂MnO₃·MnO₂ composite material is superior to that of Li₂CO₃·Li₂MnO₃ and Li₂CO₃·MnO₂. This indicates that when lithium carbonate, lithium metal oxide, and metal oxide are present simultaneously, the interaction between the three components results in superior electrochemical performance compared to composite materials of the two individual components. A comparison between Examples 1 and 4 shows that sintering in an oxygen atmosphere results in better electrochemical performance of the composite material.

[0072] All aspects, embodiments, and features of this invention should be considered illustrative in all respects and not limiting of the invention; the scope of the invention is defined only by the claims. Other embodiments, modifications, and uses will become apparent to those skilled in the art without departing from the spirit and scope of the invention as claimed.

[0073] In the preparation method of this invention, the order of the steps is not limited to the listed order. For those skilled in the art, variations in the order of the steps without creative effort are also within the scope of protection of this invention. Furthermore, two or more steps or actions can be performed simultaneously.

[0074] Finally, it should be noted that the specific embodiments described herein are merely illustrative examples of the invention and are not intended to limit the implementation of the invention. Those skilled in the art can make various modifications or additions to the described specific embodiments or use similar methods to replace them; it is neither necessary nor possible to exemplify all embodiments here. However, these obvious variations or modifications derived from the essential spirit of the invention still fall within the scope of protection of the invention, and interpreting them as any additional limitation would contradict the spirit of the invention.

Claims

1. A lithium-rich cathode material, characterized in that, The lithium-rich cathode material includes an electrochemically active material, the composition of which is based on the empirical formula aLi₂CO₃·bLi. x M y O z ·cM x1 O y1 In this expression, M is selected from one or more of Zr, Mn, Cr, Ni, Ti, Co, Ru, Sn, Mo, Fe, Ge, Te, V, Cu, Zn, and Al; a, b, and c are mole fractions, where a + b + c = 1, a ≥ 0.5, b > 0, and c > 0; x, y, z, x1, and y1 are positive integers, and Li x M y O z M x1 O y1 All of them satisfy the requirement of compound electroneutrality.

2. The lithium-rich cathode material according to claim 1, characterized in that, a=0.6~0.9, 0.05≤b≤0.3, 0.05≤c≤0.

2.

3. The lithium-rich cathode material according to claim 1, characterized in that, The electrochemical decomposition plateau voltage of the lithium-rich cathode material is ≤4.6V; When the lithium-rich cathode material is used as a positive electrode active material in a battery and is first charged within a 2.5V to 4.5V window, its charge capacity is ≥ 400 mAh / g.

4. The method for preparing the lithium-rich cathode material as described in claim 1, characterized in that, Includes the following steps: A water-soluble M salt and a water-soluble lithium salt are mixed and dissolved in water to form a mixture. A carbonic acid source is then added, and the mixture is reacted to obtain a slurry containing M carbonate and Li2CO3. The slurry is dried to obtain a powder. The powder is then sintered in air or an oxygen atmosphere to obtain the electrochemically active material.

5. The preparation method according to claim 4, characterized in that, The water-soluble M salt is one or more of the acetate of M and the oxalate of M; And / or, the water-soluble lithium salt is one or more of lithium acetate, lithium oxalate, and lithium hydroxide; And / or, the carbonic acid source is one or both of ammonium carbonate and ammonium bicarbonate; And / or, the molar ratio of water-soluble M salt to water-soluble lithium salt is 1:4 to 100; And / or, in the mixture, the concentration of water-soluble lithium salt is 0.1~2 g / mL; And / or, the molar amount of the carbonate source added is 1.05 to 2.5 times the theoretical amount of carbonate required to completely precipitate lithium ions and M ions to form the corresponding carbonate.

6. The preparation method according to claim 4, characterized in that, The reaction was carried out at 5~50℃ and 100~1000rpm with stirring for 10~200min. And / or, the drying is spray drying; And / or, the sintering temperature is 200~800℃, the heating rate is 2~8℃ / min, the sintering atmosphere is an oxygen atmosphere, and the sintering time is 1~10h.

7. The application of the lithium-rich cathode material as described in claim 1, characterized in that, The lithium-rich cathode material is used as the positive electrode active material of the positive electrode sheet of a lithium-ion battery, or the lithium-rich cathode material is added to the positive electrode sheet as a lithium supplement material.

8. A positive electrode sheet, characterized in that, It includes a positive current collector and a positive electrode layer disposed on at least one side surface of the positive current collector, wherein the positive electrode layer includes the lithium-rich positive electrode material, binder, and conductive agent as described in claim 1; Alternatively, the positive electrode sheet includes a positive current collector and a positive electrode film disposed on at least one side surface of the positive current collector. The positive electrode film includes a positive active material, a binder, a conductive agent, and a lithium supplementation additive, wherein the lithium supplementation additive is the lithium-rich positive electrode material as described in claim 1. Alternatively, the positive electrode sheet may include a positive current collector, a positive active layer, and a lithium-rich positive electrode material layer disposed on the positive active layer. The positive active layer may include a positive active material, a binder, and a conductive agent. The lithium-rich positive electrode material layer may be composed of the lithium-rich positive electrode material as described in claim 1.

9. The positive electrode sheet according to claim 8, characterized in that, In the positive electrode layer, the mass ratio of the lithium-rich positive electrode material, binder, and conductive agent is 80~96:1~10:1~10; In the positive electrode film or positive electrode active layer, the mass ratio of the positive electrode active material, binder, and conductive agent is 80~96:1~10:1~10; In the positive electrode membrane, the lithium-rich positive electrode material accounts for 0.5~10 wt% of the total mass of the positive electrode membrane; The lithium-rich cathode material layer accounts for 0.5 to 10 wt% of the total mass of the cathode active layer.

10. A secondary battery, characterized in that, The secondary battery includes a positive electrode, a negative electrode, a separator, and an electrolyte as described in claim 8 or 9.

Citation Information

Patent Citations

  • Positive electrode lithium supplement additive and preparation method and application thereof

    CN118522973A

  • Low-residual alkali Li5FeO4 and preparation method thereof

    CN119911973A